Skyrmions-based logic gates in one single nanotrack completely reconstructed via chirality barrier. Issue 12 (18th February 2022) - Yu, Dongxing; Yang, Hongxin; Chshiev, Mairbek; Fert, Albert
Abstract: Logic gates based on magnetic elements are promising candidates for logic-in-memory applications with non-volatile data retention, near-zero leakage and scalability. In such spin-based logic devices, however, the multi-strip structure and fewer functions are obstacles to improving integration and reducing energy consumption. Here we propose a skyrmions-based single-nanotrack logic family including AND, OR, NOT, NAND, NOR, XOR and XNOR that can be implemented and reconstructed by building and switching the Dzyaloshinskii–Moriya interaction (DMI) chirality barrier on a racetrack memory. Besides the pinning effect of the DMI chirality barrier on skyrmions, the annihilation, fusion and shunting of two skyrmions with opposite chirality are also achieved and demonstrated via local reversal of the DMI, which are necessary for the design of an engineer programmable logic nanotrack, transistor and complementary racetrack memory. Abstract : The study realizes complete Boolean logic gates in one single nanotrack by using Dzyaloshinskii-Moriya interaction controlled Skyrmions, providing candidates for the design of next-generation skyrmions-based logic devices and logic-in-memory applications.